Pelaksanaan Putusan Pengadilan Tipikor dan Pemulihan Aset Negara: Studi Kasus Korupsi BTS 4G Kominfo (Johnny G. Plate): Implementation of Corruption Court Decisions and State Asset Recovery: Case Study of 4G BTS Corruption at the Ministry of Communication and Information Technology (Johnny G. Plate) - Ikun, Adrianus; Berkat Zega, Juli Krisman; Eka Prastiwi, Dian (PT Yupin Felicitas Utama, 2026)
Law enforcement against corruption in Indonesia does not merely focus on the punishment of offenders but also emphasizes asset recovery as a means to restore state financial losses. This study aims to analyze the implementation of the Anti-Corruption Court (Tipikor) decision and the state asset recovery mechanism in the corruption case of the 4G Base Transceiver Station (BTS) Bakti Kominfo project involving former Minister of Communication and Informatics, Johnny G. Plate. The research employs a normative juridical method using statutory, case, and conceptual approaches. Data were obtained through literature studies of relevant legislation, court decisions, and academic writings concerning asset recovery in corruption crimes. The findings indicate that the implementation of the Tipikor court decision in the BTS 4G case has generally complied with the applicable legal framework, yet several obstacles persist during the execution phase, particularly in asset seizure and compensation payment. These challenges arise from limited asset ownership data, weak institutional coordination, and lengthy administrative procedures. Although asset recovery through confiscation, auction, and state treasury deposit has been conducted, the overall process remains suboptimal. The study recommends establishing an integrated national asset recovery system, enhancing law enforcement capacity in financial investigation and asset tracing, and strengthening public transparency in reporting recovered assets.